Currency System and Its Impact on Economic Stability - Saharuddin, Desmadi; Rama, Ali (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2017)
A number of economic problems that occurred during the power of Mamluk (1250-1517 AD) was considered as a result of the change to currency system, namely from the system of commodity-based money (gold and silver) into paper-based money (fiat). Instability prices, decrease of trading activities, high of unemployment number were a number of economic indicators that occurred at that time. This issue of macro-economy was considered as a result of changes in the money system. This study analyzes the dynamic relationship between the price of gold as a representation of commodity money system and M2 as a representation of fiat money against the stability of economic indicators such as inflation, economic growth, stock prices, and unemployment and interest rates. This study found that both systems not vary significantly against each other in its influence on macroeconomic variables. It means that the two systems do not have contrast distinction. Indeed, it was found that the commodity-based money system is not free of inflation, as propagated by the supporters of the dinar and dirham (dinarist). DOI: 10.15408/aiq.v9i2.4749